Development of the National Identity Measurement Using the Implicit Association Test Method - Christiany Suwartono; Eko A. Meinarno; Gugah Bawono (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2017)
This study is a first attempt to develop a new instrument using the Implicit Association Test (IAT) method. Researchers have tried to use this method in social psychology research, particularly to measure the construct of national identity. The national identity is a multi-dimensional construct and has several fundamental attributes, namely the same territorial, historical memories, culture, general rights laws and obligations for all members, and equal rights in the economic and territorial mobilization for group members. The study was conducted with 48 participants aged 17-23 years (M = 18.98, SD = 1.25). The result showed that the correlation between explicit and implicit measures on the construct of national identity was positive but not significant. Moreover, the explicit and implicit measurement did not provide the same pattern; indicating that both measurements measure national identity construct from a different point of view. Next, we evaluate the strengths and weaknesses of the two measurement methods in the Discussion section and then, provide recommendations for further studies.